2011
DOI: 10.1016/j.neuron.2011.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Target-Specific Remodeling of Fast-Spiking Inhibitory Circuits after Loss of Dopamine

Abstract: Summary In Parkinson disease (PD), dopamine depletion alters neuronal activity in the direct and indirect pathways and leads to increased synchrony in the basal ganglia network. However, the origins of these changes remain elusive. Because GABAergic interneurons regulate activity of projection neurons and promote neuronal synchrony, we recorded from pairs of striatal fast-spiking (FS) interneurons and direct- or indirect-pathway MSNs after dopamine depletion with 6-OHDA. Synaptic properties of FS-MSN connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
144
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(162 citation statements)
references
References 91 publications
13
144
2
Order By: Relevance
“…Thus, deletion of D2R in the MSNs mirrors the motor impairments observed by the total loss of D2Rs in D2R-null mice (Baik et al, 1995;Jung et al, 1999) and support the critical role of these receptors in modulating the activity of D2R-expressing MSNs of the indirect pathway (Gittis et al, 2011). D2R floxflox/En1Cre/ϩ mice, however, are hyperactive when exposed to a novel environment, in particular during the early phase of exploration, and hyperresponsive to DAT blockade by cocaine.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, deletion of D2R in the MSNs mirrors the motor impairments observed by the total loss of D2Rs in D2R-null mice (Baik et al, 1995;Jung et al, 1999) and support the critical role of these receptors in modulating the activity of D2R-expressing MSNs of the indirect pathway (Gittis et al, 2011). D2R floxflox/En1Cre/ϩ mice, however, are hyperactive when exposed to a novel environment, in particular during the early phase of exploration, and hyperresponsive to DAT blockade by cocaine.…”
Section: Discussionsupporting
confidence: 57%
“…Experiments in mice have revealed that chronic dopamine depletion increases the functional connectivity between striatal fast-spiking interneurons and the group of medium spiny neurons (MSNs) that project to the external segment of the globus pallidus (GPe), a part of the indirect basal ganglia pathway. These changes were shown to be sufficient to increase the synchrony between the GPe-projecting MSNs in a computer model of the striatal network incorporating interneurons and MSNs (Gittis et al, 2011). Similar findings have been made using acute pharmacological manipulations of cholinergic striatal interneurons leading to the induction of striatal beta oscillations (McCarthy et al, 2011).…”
Section: Oscillations In Corticobasal Ganglia Circuitssupporting
confidence: 62%
“…Changes in structural plasticity were detected within hours following peripheral lesions, suggesting that they might account for rapid changes in functional plasticity of receptive fields. Furthermore, dramatic changes in structural plasticity by fast-spiking striatal inhibitory neuron axons that specifically target the indirect striatal pathway were detected following lesions that result in dopamine deprivation 97 . Finally, two recent studies in sensory-deprived visual cortex provided evidence that regulation of structural plasticity by inhibitory interneurons may provide permissive conditions for subsequent plasticity by excitatory neurons.…”
Section: Inhibitory Circuit Rearrangementsmentioning
confidence: 99%